Pengaruh Komunikasi Informasi Edukasi terhadap Kunjungan Antenatal Care di Puskesmas Sungai Bilu Banjarmasin: The Effect of Communication Information Education to the Antenatal Care Visit at Puskesmas Sungai Bilu Banjarmasin - Stefanicia Stefanicia; Rena Oki Alestari (Jurnal Surya Medika (JSM), 2022)
Background: The Implementation of Midwives' activities as the spearhead of the KIA Program implementation generally showed that the implementation of midwives' activities in Antenatal Care services is still low. Objective: Analyze the effect of communication information education on the Antenatal Care visit At Puskesmas Sungai Bilu Banjarmasin. Method: Analytical survey using cross Sectional approach. The population of this research is the third-trimester pregnant who take Antenatal care visits at Puskesmas Sungai Bilu Banjarmasin from December 2017 until February 2018 which is averaged 55 people per month. The total sample is 49 pregnant. The sampling technique is using Accidental Sampling. The data collection is using a questionnaire. The data analysis is using Fisher Exact Test (α = 0,05). Finding: Given to 49 respondents, can be seen from Fisher Exact Test. Communication was not affected during the Antenatal Care visit (p= 0,110). The information was not given effect to the Antenatal Care visit (p= 0,010). Education was given effect to the Antenatal Care visit ( p= 0,05). Conclusion: Communication, Information, was not given effect to the Antenatal care visit, and Education was given effect to the Antenatal Care visit.